PERANAN GOOD UNIVERSITY GOVERNANCE TERHADAP KINERJA PERGURUAN TINGGI - zaky machmuddah; entot suhartono (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2019)
Finding emperical evidence dealt with good university governance to higher education performance is the main purpose of the current research. Survey is method used in the research. Sample used in the research is higher education lecturers in Semarang. Sampling technique used is accidental sampling. Multiple linier regression with SPSS program is used to analyse data. Findings of the research are analised and described so that they can give information related to research variable. Research findings proved that transparancy, responsibility and fairness signifcantly affected to higher education performance. Therefore, for accountability and independency variables, the relation was not significant. The research findings gave empirical evidence that good university governance had effect on higher education performance. Therefore, higher education institutions should apply good university governance to improve their performance.